The relationship of facial asymmetry and bite force to handedness in Iraqi adult sample (Mustansiria Dental Journal, 2018)
Facial asymmetry is a normal finding in clinically symmetrical faces. Theasymmetry in general was either functional and/or structural in nature. The objectiveof this study was to investigate the relationship of the amount and direction of facialasymmetry in clinically symmetrical faces with class I normal occlusion tohandedness, and to discover if there is any relation of occlusal bite force withhandedness and facial asymmetry in Iraqi Arab adult sample.The sample was 60 untreated Iraqi adult persons, 30 right handers, 30 left handersand each group consisted of 15 males and 15 females, with age range 18-25 years. Foreach subject a posteroanterior radiograph was taken, and then a maximum molar biteforce was measured digitally in the first molar area on each side.All subjects of the sample showed skeletal asymmetry although they have normalocclusion and it was significantly greater in right handers than in left handers(P